Mapping Global Trends in Digital Leadership for Quality Education: A Bibliometric and Visual Analysis From 2000 to 2025 - Imama, Mohammad Luthfi; Putranto, Rahma Huda; Wahyuningsih, Diah; Agustian, Edo; Suparman, Suparman (Universitas Muhammadiyah Surakarta, 2026)
Digital leadership has become a transformative paradigm for achieving quality education in the digital era. However, existing studies are mostly narrative and fragmented, offering limited understanding of how this concept evolves globally across educational contexts. This study provides a novel bibliometric and visual analysis of global research on digital leadership from 2000 to 2025. It differs from previous works by combining a PRISMA-guided approach with VOS viewer visualization to systematically map intellectual structures, thematic evolution, and collaboration networks in the field. A total of 647 journal articles indexed in Dimensions.ai were analyzed quantitatively to trace the development of digital leadership research related to quality education. The analysis examined publication trends, author networks, and dominant themes to identify conceptual and regional shifts. The results reveal a clear transition from technology-oriented and managerial perspectives to value-based and human-centered frameworks emphasizing ethics, inclusion, and sustainability. This study contributes to consolidating digital leadership as a multidimensional construct that bridges technology, pedagogy, and moral responsibility. The findings provide a conceptual foundation for policymakers and educational leaders to design strategies that promote adaptive, ethical, and future-ready leadership in alignment with Sustainable Development Goal 4 on quality education.